Constellation design of 32-QAM by scaling two square 16-QAMs with dual-level coding - Minhui Yu; Seunggi Choi; Hosung Park (ICT Express)
In this paper, we propose a 32-quadrature amplitude modulation (QAM) constellation to achieve high spectral efficiency, along with dual-level coding (DLC) and successive cancellation decoding (SCD). The proposed odd-bit 32-QAM constellation is designed by duplicating 16-QAM and scaling and is referred to as duplicate-and-scale QAM (DaSQAM). Analysis of bit-interleaved coded modulation (BICM) capacity demonstrates that the DaSQAM with the DLC and the SCD is better than other conventional QAMs. When using low-density parity-check (LDPC) codes, the DaSQAM shows enhanced performance in terms of bit error rate (BER) and block error rate (BLER) over the conventional QAMs.2018 The Korean Institute of Communications and Information Sciences. Publishing Services by Elsevier B.V. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/).